Розробка рекомендацiйної системи на базі нейронних мереж - Макогон, Ю. О. (ХНУРЕ, 2021)
A neural network (also an artificial neural network, ANN) is a mathematical model, as well as its software or hardware implementation, built on the principle of the organization and functioning of biological neural networks - networks of nerve cells of a living organism. This concept arose when studying the processes occurring in the brain, and when trying to model these processes. The first such attempt was the neural networks of W. McCulloch and W. Pitts. After the development of learning algorithms, the resulting models began to be used for practical purposes: in forecasting problems, for pattern recognition, in control problems, etc.
Keywords: нейронні мережі